Angiographic profile and outcomes of Pakistani women with ST elevation myocardial infarction - Sobia Masood; Kanwal Fatima Aamir; Khalid Naseeb; Quratulain Shaikh; Tahir Saghir; Syed Nadeem Qamar (Journal of the Pakistan Medical Association, 2020)
Objective: To evaluate the angiographic profile and outcome of primary percutaneous coronary intervention in female patients with acute myocardial infarction. Method: The cross-sectional study was conducted at the National Institute of Cardiovascular Diseases, Karachi, from July 1, 2017, to March 31, 2018, and comprised female patients presenting with acute myocardial infarction who underwent primary percutaneous coronary intervention and got enrolled in the National Cardiovascular Data Registry. Follow-up calls were made 1 year post-intervention and outcomes were noted. Data was analysed using SPSS 21. Results: Of the 522 female patients with a mean age of 57.41±11.14 years, 334(64%) were hypertensive, 202(38.7%) diabetic, 16(3.1%) had a family history of coronary artery disease, and 9(1.7%) were smokers. Single-vessel disease was observed in 183(35.1%) patients, and three-vessel disease in 144(27.6%). Post-procedure thrombolysis in myocardial infarction flow (0-II) was observed in 29(5.6%) patients, bleeding in 2(0.4%), and in-hospital mortality was in 22(4.2%). Telephonic follow-up was successfully conducted in 436(87.5%) of the discharged patients, and, of them 15(3.4%) had expired and recurrence was reported by 10(2.3%) patients and 8(80%) of them underwent re-intervention. Conclusion: More than half the female patients had multi-vessel disease and bifurcation lesion was observed in more than three-fourth of the sample. Key Words: Coronary artery disease, Women, Percutaneous coronary intervention, Acute myocardial infarction, Angiography, Pakistan. Continuous...